Examination of Magnesium, Calcium, Phosphorus, and Albumin Levels in Critically Ill Patients (intubated or admitted to the intensive care unit) Poisoned with Organophosphorus Poisons - Samsamshariat, Shiva; Maghami-Mehr, Asieh; Salehi, Zahra; Forghani, Mohsen; Zoofaghari, Shafeajafar (International Journal of Medical Toxicology and Forensic Medicine, 2025)
Background: Poisoning with organophosphates (OP), one of the most common types of poisoning, can lead to decreased levels of calcium, magnesium, phosphorus, and albumin. Lower levels of these elements may help improve patient outcomes and reduce mortality rates. Since few studies have explored how these serum element levels change in patients poisoned with OP, this study aims to examine magnesium, calcium, phosphorus, and albumin levels in critically ill patients poisoned with OP. Methods: This cross-sectional study included 89 critically ill patients (intubated or admitted to the intensive care unit) poisoned with various OP agents (including Chlorpyrifos (CPF), Diazinon (DZN), Malathion (MLT), and others) and hospitalized at Khorshid Hospital in Isfahan from 2013 to August 2023. Demographic and clinical data, along with magnesium, calcium, phosphorus, and albumin levels on days 1, 3, and 5, were extracted from patients’ records and documented. Results: Examination of changes in magnesium, calcium, phosphorus, and albumin levels on days 1, 3, and 5 after hospitalization showed a significant downward trend in magnesium, calcium, and phosphorus levels in MLT poisoning (P-value < 0.001). In CPF poisoning, DZN levels decreased from day one to day three and then increased. Patients’ albumin levels also declined significantly over five days of treatment in cases of CPF, DZN, and MLT poisoning (P-value < 0.05). Additionally, a calcium reduction within five days of hospitalization increased the risk of death by 3.983 times (P-value = 0.013). Magnesium reduction significantly raised the risk of death (OR: 1.621; P-value = 0.044). However, reductions in phosphorus and albumin did not show a significant relationship with mortality (P-value > 0.05). Conclusion: Severe OP poisoning results in a reduction in magnesium, calcium, phosphorus, and albumin levels over a period of five days. The reduction was more pronounced in MLT poisoning. Additionally, decreased levels of calcium, magnesium, phosphorus, and albumin increased the risk of death, although this effect was only significant for calcium and magnesium.